A critical analysis of the literature and theoretical perspectives on theory–practice gap amongst newly qualified nurses within the United Kingdom. (August 2015) - Monaghan, Thomas
Summary: Objectives: This critical analysis of the literature examines the factors and theoretical perspectives contributing to the theory–practice gap for newly qualified nurses within the United Kingdom. This article aspires to inform, guide and promote effective nursing education both academically and practically. Design: A systematic search strategy was conducted to identify relevant literature covering the period of 2000–2014, to include only contemporary theoretical perspectives coinciding with the dearth of contemporary literature post Project 2000. Data Sources: The literature was systematically investigated utilising nursing research databases, the Cumulative Index of Nursing and Allied Health Literature, Allied and Complementary Medicine, the U.S. National Library of Medicine and Internurse. Review Methods: To satisfy the search criteria only articles conducted within the United Kingdom and written in the English language were included. Only literature including nurses and newly qualified nurses were included. To identify relevant literature a series of key words were utilised. Results: Systematic review of the literature revealed that newly qualified nurses feel unprepared for practice, lacking confidence in their own abilities. It was also felt by newly qualified nurses that not enough time was dedicated to the production of clinical skills during their training. The use of preceptorship programmes was found to reduce the transitional stress associated with becoming a qualified nursing practitioner. Conclusions: Despite the increasing research being undertaken in the area of theory–practice gap there is still a need for nursing educators, practice areas and regulatory bodies to invest further in research. The effects of preceptorship and simulation exercises in particular require more research to provide regulatory bodies with enough evidence to make an informed decision as to whether their use should be mandatory.